The Penang Buddhist Association: An Outline 1925 - 1960 - Francis, Michael S. (Universiti Sains Malaysia, 1973)
Accordingly therefore, the Penang Buddhist Association was selected. Much as its name may tend to lead one into thinking that it was an organisation representative of all Buddhists in Penang, I hasten to add that on the contrary it was not. There are several other associations catering for Buddhis ts too, among whom the Penang Buddhist Association is one of the more prominent.